Determinants for coupon redemption in video-on-demand platforms - Magalhães, Miguel Sousa Vasco Gonçalves de (2019)
Television operators are facing a greater and greater threat from streaming platforms. The fact that these services allow viewers to have more control over what they watch, when they watch it and where they watch it, has made them more attractive than traditional TV. The video-on-demand (VoD) platforms developed by tv operators are a way to compete with streaming services such as Netflix and to keep their current customers engaged in their service ecosystem. This paper analyses an email marketing campaign in which an anonymous television operator provided their customers with digital coupons to be used in its VoD platform, in exchange for their answer to a survey regarding their media behaviors and preferences. With the information on who used the coupon and with the data collected from the survey, the research focus was on the development of a model that allowed the identification of determinants for coupon redemption and also an accurate prediction of which customers would take advantage of this promotion campaign. The results obtained highlight the positive impact of these campaigns can have in retaining customers and the necessity for better targeting to improve their performance.